2017
DOI: 10.2166/wst.2017.580
|View full text |Cite
|
Sign up to set email alerts
|

Initial conditions of urban permeable surfaces in rainfall-runoff models using Horton's infiltration

Abstract: Infiltration is a key process controlling runoff, but varies depending on antecedent conditions. This study provides estimates on initial conditions for urban permeable surfaces via continuous simulation of the infiltration capacity using historical rain data. An analysis of historical rainfall records show that accumulated rainfall prior to large rain events does not depend on the return period of the event. Using an infiltration-runoff model we found that for a typical large rain storm, antecedent conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…This runoff generation process is referred to as the saturation-excess runoff. Q/P (%) of a watershed will become larger when effective soil water-storage is reducing [19][20][21][22]. Even a medium-sized storm event over a saturated watershed with a high runoff coefficient may cause severe flooding; therefore, it is critical to assess the performance of different runoff models under different runoff coefficient conditions in order to select the best performing parsimonious urban rainfall-runoff model for urban runoff estimation.…”
Section: Methodology and Study Sitementioning
confidence: 99%
“…This runoff generation process is referred to as the saturation-excess runoff. Q/P (%) of a watershed will become larger when effective soil water-storage is reducing [19][20][21][22]. Even a medium-sized storm event over a saturated watershed with a high runoff coefficient may cause severe flooding; therefore, it is critical to assess the performance of different runoff models under different runoff coefficient conditions in order to select the best performing parsimonious urban rainfall-runoff model for urban runoff estimation.…”
Section: Methodology and Study Sitementioning
confidence: 99%
“…Contrarily, some reported that the usage of CN in representing a watershed is often contradictory in describing related land cover areas [13]. Some researchers still reported difficulty to calibrate the existing model [14,15] while other studies started to incorporate soil moisture and saturation-excess concepts in their modelling approach [16][17][18][19]. US researchers [2,20] were first to conduct large scale studies on the SCS CN model by analyzing more than half a million rainfall events across 24 states in the USA and reported an optimum λ = 0.05 to achieve better runoff modelling results than Equation (2) in USA.…”
Section: Introductionmentioning
confidence: 99%
“…This may indicate that either the initial loss in the model needs to be differentiated according to soil moisture, which indicates a parameter assessment error, or that the imperviousness is lower for events with a low soil moisture content, which indicates a process knowledge error. Without giving a precise answer, we refer to the literature dealing with this specific knowledge gap in urban drainage modelling (Thorndahl et al 2008;Davidsen et al 2018;Nielsen et al 2019).…”
Section: Signatures and Surrounding States Illustrating Process Knowl...mentioning
confidence: 99%